ANALISIS PERBEDAAN PERSEPSI PASIEN PESERTA BPJS TERHADAP PENILAIAN MUTU PELAYANAN DI PUSKESMAS KEDUNGMUNDU KOTA SEMARANG TAHUN 2016 - Clara Sylvia Pardede; Chriswardani Suryawati; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
BPJS Health in collaboration with the health facilities facilities such as health centers, neighborhood health center and the hospital to open the doors of public health services. Puskesmas as FKTP need to see how the analysis of satisfaction felt by participants BPJS. Every person has the same right to gain access to resources in the health sector. This study aimed to analyze the differences in the perception of patients BPJS using service quality dimensions. This study uses descriptive quantitative research subjects were taken by using purposive sampling. As for the study is based on the quality dimension, namely the quality of tangibles, reliability, responsiveness, assurance, emphaty. The patients studied were BPJS PBI and Non PBI get service in Puskesmas Kedungmundu Semarang with sample sizes of 50 BPJSPBI and 50 BPJS Non PBI. The result of this research is that the quality of tangible (p = 0.03), reliability (p = 0.10), responsiveness (p = 0.10), assurance (p = 0.55), empathy (p = 0.8).The conclusion of this study is the discrepancy between the patient's perception BPJS PBI dan Non PBI BPJS seen from the dimensions of quality of tangibles ( p <0.05 ) and no differences were seen from the perception of quality dimensions of reliability , responsiveness, assurance and assurance( p > 0.05 ) , Suggestions for workers to always be friendly , patient , polite and cautious in serving patients and always keeping the environment clean.